Fulfillment of The Right to Clean Water for Post-Disaster Communities in Gumbasa District, Sigi Regency - Rosdian Rosdian; Ikbal Ikbal; Abraham Kekka (Administrative and Environmental Law Review, 2022)
Water is a basic human need; no one can live without water. As a basic need, water is part of the requirements for an adequate standard of living for the health and well-being of all human beings. The problem currently being faced is that the availability of clean water to meet the needs of the people of Gumbasa District is decreasing after the earthquake in Sigi Regency. On the one hand, there is a view that water is a commodity (economic good), while on the other hand, it is said that water is a social good. This article aims to analyze the progress of regulating the right to water as a human right and efforts to fulfill and provide clean water after the disaster in Gumbasa District, Sigi Regency. The research method uses a normative juridical method, which analyzes library materials or secondary data. The research results show that the right to clean water implies that everyone must access water without discrimination. The role of the Sigi Regency Government is essential when people are not in the same position in getting water; the difference in each person's position is not only due to the problem of economic inequality but also to the natural conditions that exist in a particular area. These differences make it difficult for some parts of the community to access clean water, especially the fulfillment of clean water sources after the disaster.